EFEKTIVITAS PEMBERIAN PRO BONO DI POS BANTUAN HUKUM PENGADILAN NEGERI DENPASAR Oleh - Galguadi, G. Andika; Arthani, Ni Luh Gede Yogi (Fakultas Hukum, Universitas Mahasaraswati Denpasar, 2024)
The enactment of the Legal Aid Law is an effort to uphold the right of every Indonesian citizen to access justice and receive fair and impartial judicial treatment. The establishment of a Legal Aid Post (Posbakum) functions as a mechanism to ensure fair legal protection. Functioning as a key player in providing public legal services, Posbakum is committed to providing high-quality assistance and safeguarding the legal rights of all beneficiaries. Various scientific records have highlighted examples where Posbakum, particularly in certain regions in Indonesia, faced operational inefficiencies. This scenario extends to Posbakum which is affiliated with the Denpasar District Court. The main focus of This investigation revolved around examining the implementation and outreach efforts of the Denpasar District Court Posbakum, in addition to evaluating the efficacy of its legal aid provisions. Using qualitative methodology, this research is a field investigation that combines interview sessions and document analysis for data collection. The primary data source consists of insights derived from interviews, while additional information is gathered from relevant documentation and related sources. Data monitoring includes the process of condensation, presentation, and conclusive conclusions. This study concludes that the Denpasar District Court Posbakum operates quite effectively, although with room for further optimization in its functions. This situation is caused by persistent obstacles in the service delivery framework, originating from community dynamics, available resources, infrastructure constraints, cultural influences, and operational efficacy.